2017
DOI: 10.1007/s11301-017-0125-3
|View full text |Cite
|
Sign up to set email alerts
|

International project finance: review and implications for international finance and international business

Abstract: This literature review analyzes the global phenomenon of international project finance (PF) as both a management and finance instrument, allowing practitioners to realize large scale infrastructure projects in high risk contexts. After describing the characteristics of PF, its historical origins and its unique benefits for empirical inquiry, I summarize the findings of academic research from an interdisciplinary perspective. Based on this integration of Finance, Management and International Business research, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 146 publications
(180 reference statements)
0
21
0
Order By: Relevance
“…Hainz and Kleimeier (2012) conducted a study across 64 countries and showed that nonrecourse project finance supported by syndication of development banks offers effective mitigation to sovereign risks. Müllner (2017) called for interdisciplinary research for project finance based on integration of finance, management, and international business.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Hainz and Kleimeier (2012) conducted a study across 64 countries and showed that nonrecourse project finance supported by syndication of development banks offers effective mitigation to sovereign risks. Müllner (2017) called for interdisciplinary research for project finance based on integration of finance, management, and international business.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Another issue that stands out in the results of the studies examining the financing decisions of the projects to a large extent is market risk. In its shortest definition, market risk is the possibility of loss of firms due to price movements in the market [44]. For example, if the foreign exchange rate is overvalued, firms with high foreign exchange debt may suffer too much loss.…”
Section: Literature Review On the Financing Of Large-scaled Projectsmentioning
confidence: 99%
“…The details of them are given on Table 1. Müllner [44] In this framework, dimensions and criteria are selected based on BSC approach. This approach was used by many different researchers in the literature with various purposes.…”
Section: Identifying the Dimensions And Criteriamentioning
confidence: 99%
“…Project financing takes place internationally [3]. It is a global phenomenon, complex and multifaceted [4]. Investors aim for profit.…”
Section: Basics: Infrastructure Project Financementioning
confidence: 99%
“…-The European Union will combine a principled approach to connectivity and the recognition -quite in the sense of our approach of intercultural project finance -that Asia encompasses different regions, which are home to very diverse countries in terms of economic models and level of development. It is a matter of concrete actions, based on three strands: 4 1. Creating transport links, energy and digital networks, and human connections: Efficient infrastructure and connections create growth and jobs and enable people and goods to move.…”
Section: Three Core Approaches For Implementationmentioning
confidence: 99%